The Effect of Roundtable Technique on The Students’ Ability in Writing Descriptive Text at Seventh Grade Students in UPTD SMP Negeri 10 Pematangsiantar - Lasri Nababan, Dian; Sitanggang, Anita; Saut Raja Sihombing, Partohap (The Future of Education Journal, 2024)
This research was conducted to investigate the effect of the Roundtable Technique on students' ability to write descriptive texts in grade seven at UPTD SMP Negeri 10 Pematangsiantar. The methodology employed in this study was quantitative. The population consisted of seventh-grade students at UPTD SMP Negeri 10 Pematangsiantar for the academic year 2024/2025. The researcher selected two classes as samples: VII-5 served as the experimental group, comprising 30 students, and VII-4 acted as the control group, also consisting of 30 students. Data were collected through pre-tests and post-tests administered to both groups. The mean score for the experimental class on the pre-test was 50.70, while the control class had a mean score of 48.70. Conversely, the mean score for the experimental class on the post-test was 75.70, compared to 63.43 for the control class. To gather data, the researcher utilized tests as instruments. The t-test result was 3.676>1.672 at the 5% significance level. This outcome indicates that the alternative hypothesis (Ha) was accepted, while the null hypothesis (Ho) was rejected. Therefore, it can be concluded that the Roundtable Technique has a significant effect on the writing abilities of seventh-grade students at UPTD SMP Negeri 10 Pematangsiantar.